Rendemen dan Komposisi Kimia Biji Sorgum yang disosoh dengan Alat Sosoh Batu Gurinda - S. Iskandar; D. Zainuddin; I.P. Kompiang (Buletin Ilmu Makanan Ternak, 1991)
Nutritive value of sorghum grain can be improved by separating the pericarp (bran) from its endotherm (polished grain) with grindstone polisher. Laboratory scale grindstone polisher, "SATAKE" was used to polish three varieties of dark sorghum grain of No. 46, No. 6C and UPCA-S2. They were subjected to different polishing time (1, 2 and 3 minutes) and moisture content (10%, 12% and 14%). Variety and polishing time significantly (P<0.05) affected the parameters. Polished grain recovered decreased from 60% polished in one minute to 36% in three minutes. More than 88% tannin was removed. About 40% of protein was removed in one minute polishing and 60% was in three minutes. About 56% of ADF was also removed in one minute and 68% in three minutes polishing. Moisture content of the whole grain did not seem significantly to affect all parameters. It is concluded that in order to separate the pericarp from its endotherm of sorghum grain, grindstone polisher can effectively be used. Key words: Sorghum, polishing, yield, chemical composition.